Implementation of Bank Indonesia Policy on the Mandatory Use of Rupiah in Indonesian Border Areas (Case Study in Sebatik Tengah Subdistrict, Nunukan Regency) - Supardi, Yusril Ihza Putra; Moh.Ikhwan Syahtaria; Yulian Azhari; Rachmat Setyawibawa; Arifuddin Uksan (International Journal of Economics, Business and Innovation Research, 2025)
Community encouragement to fulfill their basic needs requires border communities to find solutions to the conditions of the border areas which are still lacking. This situation requires that economic transactions in the border region tend to depend on Malaysian products, as a result of the dominance of foreign currency (ringgit) in the Central Sebatik District that cannot be avoided. Therefore, this research is titled "IMPLEMENTATION OF BANK INDONESIA POLICY ON THE OBLIGATION TO USE RUPIAH IN INDONESIA BORDER REGION (Case Study in Central Sebatik District of Nunukan Regency)". The purpose of this research is to explain and analyze how Bank Indonesia's policy on the obligation to use rupiah in Indonesia's border area is implemented, as well as the implementation of policies and efforts to overcome the problem. This research uses a descriptive qualitative method with an inductive approach. Data collection techniques include interviews, observation, and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. In this research, researchers used the Van Meter and Van Horn theory of implementation with six dimensions, namely Objectives and Measures, Resources, Communication and Implementation activities, Implementing Agency Characteristics, Economic, Social and Political Environment, and Implementing Tendencies. The results of this research show that the implementation of Bank Indonesia's policy on the obligation to use rupiah in the Indonesian border region (Case study in Central Sebatik District) has been running quite well, but the results have not been optimal because there are still several obstacles that become obstacles such as fluctuations in the exchange rate experienced a change, the dependence of the trade sector and product marketing as well as the supply of needed goods from Malaysia, low public awareness of existing policies, limited infrastructure and facilities, resource management has not been well coordinated, lack of coordination between agencies and instruments involved in the policy. Therefore, researchers suggest that socialization activities should be conducted more frequently, there should be good coordination between institutions, and a dedicated team should be established to focus on the economy and financial system (payment system), human resource development, development of supporting facilities and infrastructure, and creation of a new economic center.